Factors associated with sentinel lymph node status and prognostic role of completion lymph node dissection for thick melanoma. Issue 2 (February 2020) - Boada, Aram; Tejera-Vaquerizo, Antonio; Ribero, Simone; Puig, Susana; Moreno-Ramírez, David; Quaglino, Pietro; Osella-Abate, Simona; Cassoni, Paola; Malvehy, Josep; Carrera, Cristina; Pigem, Ramon; Barreiro-Capurro, Alicia; et al.
Abstract: Introduction: Sentinel lymph node (SLN) biopsy is useful for the prognostic stratification of patients with thick melanoma. Identifying which variables are associated with SLN involvement and establishing risk in different subgroups of patients could be useful for guiding the indication of SLN biopsy. The value of complete lymph node dissection (CLND) in patients with a positive SLN biopsy is currently under debate. Materials and methods: To identify factors associated with SLN involvement in thick melanoma we performed a multicentric retrospective cohort study involving 660 patients with thick melanoma who had undergone SLN biopsy. To analyze the role of CLND in thick melanoma patients with a positive SLN biopsy, we built a multivariate Cox proportional hazards model for melanoma-specific survival (MSS) and disease-free survival (DFS) and compared 217 patients who had undergone CLND with 44 who had not. Results: The logistic regression analysis showed that age, histologic subtype, ulceration, microscopic satellitosis, and lymphovascular invasion were associated with nodal disease. The CHAID (Chi-squared Automatic Interaction Detection) decision tree showed ulceration to be the most important predictor of lymphatic involvement. For nonulcerated melanomas, the histologic subtype lentigo maligna melanoma was associated with a low rate of SLN involvement (4.3%). No significant differences were observed for DFS and MSS between the CLND performed and not-performed groups. Nodal status on CLND was associated with differences in DFS and MSS rates. Conclusion: We identified subgroups of thick melanoma patients with a low likelihood of SLN involvement. CLND does not offer survival benefit, but provides prognostic information.